2021
DOI: 10.3390/s21155091
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle Array Electrode-Based Wearable EMG System for Detection of Driver Drowsiness through Steering Wheel Grip

Abstract: Driver drowsiness is a major cause of fatal accidents throughout the world. Recently, some studies have investigated steering wheel grip force-based alternative methods for detecting driver drowsiness. In this study, a driver drowsiness detection system was developed by investigating the electromyography (EMG) signal of the muscles involved in steering wheel grip during driving. The EMG signal was measured from the forearm position of the driver during a one-hour interactive driving task. Additionally, the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…Several reports on microneedles (MNs) have been published in the past decade due to their attractive features such as being minimally invasive for painless sampling and micron-size dimensions limiting their penetration to the intradermal space, thanks to the MEMS fabrication technology [ 21 , 22 ]. To date, MNs have been used for transdermal drug delivery [ 23 ], insulin injection [ 24 ] and for sensing various analytes of clinical interest lactate [ 25 ], glucose [ 22 ], L-DOPA [ 26 ], glutamate [ 27 ] and cholesterol [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports on microneedles (MNs) have been published in the past decade due to their attractive features such as being minimally invasive for painless sampling and micron-size dimensions limiting their penetration to the intradermal space, thanks to the MEMS fabrication technology [ 21 , 22 ]. To date, MNs have been used for transdermal drug delivery [ 23 ], insulin injection [ 24 ] and for sensing various analytes of clinical interest lactate [ 25 ], glucose [ 22 ], L-DOPA [ 26 ], glutamate [ 27 ] and cholesterol [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The eigenvector of A T A is (v w,i , i = 1, 2, 3). A is shown in Equation ( 6), and the remain three control points can be determined by Equation (7).…”
Section: Head Pose Estimationmentioning
confidence: 99%
“…Physiological signal measurement methods are usually based on the driver's physiological signals, such as electroencephalogram (EEG [5]), electrooculogram (EOG [6]), and EMG [7]. The fatigue state can be evaluated by frequency domain analysis and linear classification based on EEG or EEG.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that as the driver’s drowsiness level increased, the muscle activity for gripping the steering decreased with time while driving. In addition, the results of the frequency domain analysis revealed that the frequency components of the steering shifted from low frequency to high frequency in an hour’s driving [ 38 ]. In one case, the driver’s states were detected by electrodes attached to the steering [ 39 ] for sensing the vitals.…”
Section: Drowsiness Detection and Estimation Based On Biometric Informationmentioning
confidence: 99%